2019
DOI: 10.1104/pp.19.00839
|View full text |Cite|
|
Sign up to set email alerts
|

Alternative Splicing Provides a Mechanism to Regulate LlHSFA3 Function in Response to Heat Stress in Lily

Abstract: Heat stress transcription factors (HSFs) are central regulators of plant responses to heat stress. Their heat-induced transcriptional regulation has been extensively studied; however, their posttranscriptional and posttranslational regulation is poorly understood. In a previous study, we established that there were at least two HSFA3 homologs, LlHSFA3A and LlHSFA3B, in lily (Lilium spp.) and that these genes played distinct roles in thermotolerance. Here, we demonstrate that LlHSFA3B is alternatively spliced u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 52 publications
1
50
0
1
Order By: Relevance
“…In addition, the gene involved in the AS of an MYB transcription factor affects anthocyanin biosynthesis in tomato fruits, and mutations in the splice sites cause a complete loss of function in the wild-type protein [ 6 ]. Moreover, LlHSFA3B-III , an AS isoform of LlHSFA3B (heat stress transcription factors), was also found to regulate abiotic heat stress in lily plants [ 7 ]. In tea plants, an AS-associated analysis of different tissues showed that it could regulate the flavonoid pathway through certain transcription factors and functional genes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the gene involved in the AS of an MYB transcription factor affects anthocyanin biosynthesis in tomato fruits, and mutations in the splice sites cause a complete loss of function in the wild-type protein [ 6 ]. Moreover, LlHSFA3B-III , an AS isoform of LlHSFA3B (heat stress transcription factors), was also found to regulate abiotic heat stress in lily plants [ 7 ]. In tea plants, an AS-associated analysis of different tissues showed that it could regulate the flavonoid pathway through certain transcription factors and functional genes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mouse hsf1 was alternatively spliced to form four HSF1 variants, which differentially regulated the expression of chaperones (Neueder et al 2014). The LlHSFA3B gene of lily was alternatively spliced under heat stress to produce the heat-inducible splice variant LlHSFA3B-III (Wu et al 2019). Another extremely important example of AS is the Dscam gene of Drosophila melanogaster, with more than 38,000 splice variants (Schmucker et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic lines, the expression of AtMYB33 and AtMYB65 was also up-regulated, which might stem from their self-activating activity. The expression of AtMYB33, AtMYB65 , and AtCYP704B1 is independent of LoMYB33 expression, and the expression pattern of AtCYP703A2 is opposite that of LoMYB33 (Wu et al, 2019 ; Ding et al, 2021 ). We speculate that this might be explained by a negative feedback regulation mechanism involving LoMYB33 , wherein the high expression of LoMYB33 activates the feedback pathway to control the expression of these genes at a level appropriate for anther development.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then cultured with LB medium at 28 • C and 200 rpm for 3-5 h. After centrifugation and resuspending the bacteria, they were evenly spread on solid LB medium (containing 50 µg•µL −1 Kan and 100 µg•µL −1 Rif) and cultured at 28 • C for 2 days. The appropriate clones were then selected and cultured with liquid LB medium (containing 50 µg•µL −1 Kan and 100 µg•µL −1 Rif) for 12 h. The bacterial solution was resuspended with the injection buffer (10 mM MgCl 2 , 100 mM 2-morpholinoethanesulfonic acid, and 200 µM acetosyringone, pH = 5.8) and injected into tobacco leaves (Wu et al, 2019). After 48 h, the GFP signal was observed with a laser scanning confocal microscope (LSM800, Zeiss, Germany).…”
Section: Subcellular Localization Analysismentioning
confidence: 99%